(untitled) (Heritage, 2024)
The paper discusses the pioneering endeavor of Nikola (Nestor) Popovich (1833–1884) as the editor of the first church magazine in Serbia. After returning from Russia, where he was studying, he made progress and became the important religious and cultural worker in Serbia. He taught as a professor at the Gymnasium and Theological College in Belgrade, and for a time he was the religious teacher of the minor Milan Obrenovich, the future king of Serbia. He became the rector of the seminary and finally the bishop of Nish. Understanding the growing need to start a religious magazine, he found the publication Pastir [Shepherd]: a magazine for science and literature with religious content, whose editor he was during its existence between 1868 and 1870. Magazine had readers not only in the then Principality of Serbia, but also among the interested clergy and believers in the Ottoman Empire (in Old Serbia) and especially in the area of ​​the Austro-Hungarian Monarchy (the Metropolitanate of Karlovci). Regardless of the understandable lacks characteristic for every beginning, the importance of the magazine under Popovichʼs editorship is reflected in the fact that he managed to lay the foundations and pave the way for further continuous church periodical publishing in Serbia.